Optimization of size controlled poly (lactide-co-glycolic acid) nanoparticles using quality by design concept - Acharya, Dr. Sanjeev R. (Asian Journal of Pharmaceutics (AJP), 2015)
Quality by design (QbD) is a risk management and science-based approach laid down by the ICH as well as otherÂ Regulatory agencies to enhance pharmaceutical development throughout a productâ€™s lifecycle. Poly(lactide-co-glycolicÂ acid) (PLGA) is the material of choice for development of depot particulate formulations due to its biodegradable natureÂ and is also considered as the â€˜greenâ€™ eco-friendly material due its biocompatibility and non-toxic properties. Further, PLGAÂ based formulations are approved by regulatory agencies and currently in clinical practice.The aim of the current investigationÂ involves formulation, optimization and in vitro characterization of size controlled PLGA based nanoparticles by employingÂ modified nanoprecipitation technique. An initial risk-assessment analysis was conducted with different formulation andÂ process variables along with their impact on critical quality attributes of the formulation which were identified as particle sizeÂ and percentage process yield. The Ishikawa diagram was employed to determine the potential risk factors and subsequentlyÂ optimized by statistical experimental design concept. Boxâ€“Behnken design was utilized to optimize nanoparticles and furtherÂ characterizing the optimized nanoparticulate formulation in vitro. From the present study, it can be concluded that PLGAÂ based nanoparticles with controlled particle size and process yield can be obtained by inculcating the concept of QbD inÂ the product development. Key words: Boxâ€“Behnken design, nanoprecipitation technique, particle size, poly(lactide-co-glycolic acid), quality by design